Pro Tools 7 session secrets : - Hirsch, Scott (Wiley Publishing, 2006)
This practical guide from two certified Pro Tools experts begins where most other Pro Tools books leave off--it's like having a high-level, hands-on studio session with your very own seasoned audio pros! Jump in anywhere and discover the professional techniques and tricks you need to get recordings right the first time, every time